Electronic Publishing : the evolution and economics of a hybrid journal. - Brailsford, David F. (1997)
The technical, social and economic issues of electronic publishing are examined by using as a case study the evolution of the journal Electronic Publishing Origination, Dissemination and Design (EP-odd) which is published by John Wiley Ltd. The journal is a `hybrid' one, in the sense that it appears in both electronic and paper form, and is now in its ninth year of publication. The author of this paper is the journal's Editor-in- Chief. The first eight volumes of EP-odd have been distributed via the conventional subscription method but a new method, from volume 9 onwards, is now under discussion whereby accepted papers will first be published on the EP-odd web site, with the printed version appearing later as a once-per-volume operation. Later sections of the paper lead on from the particular experiences with EP-odd into a more general discussion of peer review and the acceptability of e-journals in universities, the changing role of libraries, the sustainability of traditional subscription pricing and the prospects for `per paper' sales as micro-payment technologies become available.